Advanced Vehicle Dynamics - Jazar, Reza N. (Springer International Publishing : Imprint: Springer, 2019)
This book covers the principles and applications of vehicle handling dynamics from an advanced perspective in depth. The methods required to analyze and optimize vehicle handling dynamics are presented, including tire compound dynamics, vehicle planar dynamics, vehicle roll dynamics, full vehicle dynamics, and in-wheel motor vehicle dynamics. The provided vehicle dynamic model is capable of investigating drift, sliding, and other over-limit vehicle maneuvers. This is an ideal book for postgraduate and research students and engineers in mechanical, automotive, transportation, and ground vehicle engineering. Covers many applications of vehicle handling dynamics from an advanced perspective; Broadens readers' understanding of the mathematical prediction of the dynamic behavior of vehicles for full vehicle models; Reviews the required methods to analyze and optimize vehicle handling dynamics, including vehicle planar dynamics, full vehicle dynamics, vehicle roll dynamics, and more.